2013
DOI: 10.1159/000350134
|View full text |Cite
|
Sign up to set email alerts
|

Liver X Receptor a Inhibits Osteosarcoma Cell Proliferation through Up-Regulation of FoxO1

Abstract: Background: Osteosarcoma is the most common primary bone malignancy of adolescents and young adults. Methods: We analyzed liver X receptor α (LXRα) mRNA expression in 16 pairs of human osteosarcoma tissues and adjacent noncancerous tissues. Moreover, we investigated LXRα's potential role in regulating cell proliferation in Saos-2 and U2OS cells. Results: We found that activation of LXRα, a member of nuclear receptor, was able to inhibit cell proliferation in Saos-2 and U2OS cells. At the molecular level, our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…In lung cancer, FOXO1 negatively regulated activated EGFR signaling in both cell culture and in vivo models [25] and induction of FOXO1 by curcumin inhibited lung cancer progression and metastasis [26]. Moreover, in OS cells, FOXO1 expression status was negatively associated with proliferation [27]. Given the tumor suppressor role of FOXO1, in the present study, we found FOXO1 showed a converse expression pattern of miR-135b, and overexpression of FOXO1 significantly inhibited OS cells proliferation and invasion.…”
Section: Discussionsupporting
confidence: 56%
“…In lung cancer, FOXO1 negatively regulated activated EGFR signaling in both cell culture and in vivo models [25] and induction of FOXO1 by curcumin inhibited lung cancer progression and metastasis [26]. Moreover, in OS cells, FOXO1 expression status was negatively associated with proliferation [27]. Given the tumor suppressor role of FOXO1, in the present study, we found FOXO1 showed a converse expression pattern of miR-135b, and overexpression of FOXO1 significantly inhibited OS cells proliferation and invasion.…”
Section: Discussionsupporting
confidence: 56%
“…*p<0.05 Here, we just focused on the direct targets downstream of miR-183 in controlling cell growth. Since FoxO1 plays a critical role in cell-cycle control [19,20] and has been shown to express in lung cells, we thus examined whether miR-183 may inhibit the expression of FoxO1. We either overexpressed or inhibited miR-183 expression in NSCLC cells, which decreased or increased the protein levels of FoxO1, respectively, without affecting FoxO1 transcript levels.…”
Section: Discussionmentioning
confidence: 99%
“…In the past years, the advances in chemotherapy has assisted general surgery to substantially improve the long-term survival of patients with nonmetastatic OS. However, the survival rate for patients with metastatic OS remains low [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%